2009
DOI: 10.1016/j.ppnp.2008.12.041
|View full text |Cite
|
Sign up to set email alerts
|

QCD equation of state: Physical quark masses and asymptotic temperatures

Abstract: Within a phenomenological quasiparticle model, the quark mass and temperature dependence of the QCD equation of state is discussed and compared with lattice QCD results. Different approximations for the quasiparticle dispersion relations are employed, scaling properties of the equation of state with quark mass and deconfinement temperature are investigated and a continuation to asymptotically large temperatures is presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…This is complicated, though, by the fact that we have just shown that the Breit-Wheeler is peculiarly coupled to the low-energy regime. To get a qualitative idea of the impact of the effects neglected, consider that one of the most important non-perturbative effects of a thermal background is to introduce a ''thermal mass'' to the constituent particles, 𝑚 th ∶= 𝜇𝑘 𝐵 𝑇 𝛾 ∕𝑐 2 , where 𝜇 ∼ √ 𝛼 [9,11,12]. (Taking this to be the only thermal adjustment of the dispersion relations becomes a good approximation in the hard momentum regime.)…”
mentioning
confidence: 99%
“…This is complicated, though, by the fact that we have just shown that the Breit-Wheeler is peculiarly coupled to the low-energy regime. To get a qualitative idea of the impact of the effects neglected, consider that one of the most important non-perturbative effects of a thermal background is to introduce a ''thermal mass'' to the constituent particles, 𝑚 th ∶= 𝜇𝑘 𝐵 𝑇 𝛾 ∕𝑐 2 , where 𝜇 ∼ √ 𝛼 [9,11,12]. (Taking this to be the only thermal adjustment of the dispersion relations becomes a good approximation in the hard momentum regime.)…”
mentioning
confidence: 99%